An en face swept source optical coherence tomography study of the vitreous in eyes with anterior uveitis. Issue 3 (4th July 2021) - Pichi, Francesco; Neri, Piergiorgio; Hay, Steven; Parrulli, Salvatore; Zicarelli, Federico; Invernizzi, Alessandro
Abstract: Purpose: To analyse vitreous anatomy patients with anterior uveitis (AU) using swept source optical coherence tomography (SS‐OCT). Methods: Patients with newly diagnosed AU and healthy participants were scanned using 16‐mm SS‐OCT B‐scans and 12 × 12 mm cube centred at the fovea. Linear SS‐OCT scans were evaluated to identify the premacular bursa (PB) above the macula and the Cloquet's canal above the optic disc. A dynamic evaluation of the 12 × 12 mm cube enabled en face measurement of the vertical and horizontal diameters of the PB and the presence/absence of communication between the PB and Cloquet's canal. Results: One hundred and thirty‐five subjects were included in the study. Forty‐five patients were healthy (mean age 33.47 years). En face measurements of the horizontal and vertical PB mean diameters were 5.2 mm and 4.7 mm. In 90 subjects with AU (mean age 30.10 years), the mean horizontal and vertical diameter of the PB were significantly larger (p < 0.01). Thirty‐seven eyes with AU presented with cystoid macular oedema (CME). The mean diameters of the PB in this subgroup were significantly larger (p < 0.01). In 75% of the entire cohort (51% of eyes in the control group, 87% of eyes with AU and 100% of eyes with AU and CME), a channel connecting the PB and Cloquet's canal could be identified. Conclusions: SS‐OCT identification of a connecting channel between the PB and the Cloquet's canal suggests that inflammatory cytokines may drain from the anterior chamber through this system of channels, thus increasing the risk of CME.